A Potential Combination Therapy of Berberine Hydrochloride With Antibiotics Against Multidrug-Resistant Acinetobacter baumannii - Li, Xiaobo; Song, Yanqing; Wang, Lina; Kang, Guangbo; Wang, Ping; Yin, Huabing; Huang, He (Frontiers in Cellular and Infection Microbiology, 2021)
Multidrug-resistant (MDR) Acinetobacter baumannii strains can cause severe infections in intensive care units, and are rapidly developing resistance to the last-resort of existing antibiotics, posing a major global threat to health care system. Berberine hydrochloride (BBH), a kind of isoquinoline alkaloids extracted from Berberis and other plants, has been widely used as an antibacterial medicine for its reliable therapeutic efficiency. The in vitro synergistic effects of BBH with antibiotics against MDR A. baumannii were determined. BBH alone had weak antimicrobial activity (e.g., MIC≥256 mg/L) against MDR A. baumannii. However, it dramatically increased the susceptibility of MDR strains against antibiotics with FICI values <0.5, even reversed their resistance to antibiotics (e.g., tigecycline, sulbactam, meropenem and ciprofloxacin). In vivo study has suggested BBH with sulbactam had stronger antimicrobial efficiency than monotherapy in a neutropenic murine thigh infection model. The antibiotic-sensitizing mechanism of action of BBH was evaluated as well. BBH boosted adeB gene expression and bound to the AdeB transporter protein, resulting in low uptake of BBH, which may contribute to less extrusion of antibiotics by the AdeABC pump. Knockout of the adeB gene increased uptake of BBH and diminished the antibiotic sensitization and synergistic effects between antibiotics and BBH in MDR strains. Together, BBH effectively re-sensitizes this MDR pathogen to a range of antibiotics that have become barely effective due to antibiotic resistance, which indicates BBH may be a promising therapeutic adjuvant candidate to combat MDR A. baumannii.